'Plainly of Considerable Moment in Human Society': Francis Hutcheson and Polite Laughter in Eighteenth-Century Britain and Ireland. (October 2020) - Davison, Kate
Abstract: This article focuses on Francis Hutcheson's Reflections Upon Laughter, which was originally published in 1725 as a series of three letters to The Dublin Journal during his time in the city. Although rarely considered a significant example of Hutcheson's published work, Reflections Upon Laughter has long been recognised in the philosophy of laughter as a foundational contribution to the 'incongruity theory' – one of the 'big three' theories of laughter, and that which is still considered the most credible by modern theorists. The article gives an account of Hutcheson's text but, rather than evaluating it solely as an explanation of laughter, the approach taken is an historical one: it emphasises the need to reconnect the theory to the cultural and intellectual contexts in which it was published and to identify the significance of Hutcheson's arguments in time and place. Through this, the article argues that Hutcheson's theory of laughter is indicative of the perceived significance of human risibility in early eighteenth-century Britain and Ireland and, more broadly, that it contributed both to moral philosophical debate and polite conduct guidance.